Genetic mechanism of low resistivity in high-mature marine shale: Insights from the study on pore structure and organic matter graphitization. (October 2022) - Xue, Zixin; Jiang, Zhenxue; Wang, Xin; Gao, Zhiye; Chang, Jiaqi; Nie, Zhou; Li, Hui; Wu, Wei; Qiu, Hengyuan; Wang, Qianyou; Hao, Mianzhu; Chen, Ruihua; et al.
Abstract: Low-resistance shale reservoirs have prospected in many high-mature shale gas plays with distinct yields. It is worth investigating the reasons for the difference in the production of low-resistance shale. And this needs to start from the genetic mechanism of shale low resistance. The genesis of shale low resistance is currently considered to be closely related to high-mature organic matter, which is the most important storage space for shale gas. Therefore, it is necessary to study the relationship among organic matter properties, pore structure of shale reservoir space, and shale resistivity. Herein, the typical low-resistivity shale in southern China was examined using X-ray photoelectron spectroscopy, gas adsorption, high-pressure mercury intrusion porosimetry. The results show that compared with conventional resistivity shale, low resistivity shale has smaller pore volume and specific surface area and higher organic matter graphitization degree. The high degree of graphitization significantly reduces the rock resistivity. In addition, graphitization changes the mechanical properties of organic matter. Under the action of compaction and tectonic movement, the macropores decrease sharply, the mesopores increase first and then decrease, and the micropores change little with the degree of graphitization. The change in the size and shape of the organic pores results in the collapse of the organic pores and the contact of the pore walls, which further increases the migration path of the electronic currency on the conductive organic matter and makes the rock resistivity lower. When the degree of graphitization exceeds 15%, poor pore development leads to lower resistivity, and due to poor reservoir space, such shales are extremely risky for exploration. Highlights: The OM graphitization degree has been quantified according to relative content of carbon-containing compounds' bond energy. The shale resistivity tends to decrease linearly with the increase of organic graphitization degree. TheOM graphitization leads to collapse and closure of organic pores, which reduces the pore size and pore space. The combination of graphitized OM and OM pore wall contact is responsible for the high-mature low resistivity shale.